Ila dan Zhihar Perspektif Tafsir Ayat Gender - Yeni Novitasari; Revanda Yunianti; Sabilla Wirdatul Jannah (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
Abstract: Ila and Zhihar are one of the reasons for the breakup of marriages during the ignorance. Ila is the husband's oath not to have sex with his wife anymore. At the same time, Zhihar is the husband's words which equate his wife's back with his mother's. In the past, husbands were arbitrary towards their wives—Ila during the jahiliyyah period of more than two years. So the wife is hanged not given certainty in a long time. Likewise with Zhihar during the ignorance. Husbands arbitrarily send their wives away and make it a marriage break. After going down verses 226- 227 QS. Al-Baqarah about ila, then the husband who makes ila his wife is given a challenging period of 4 months. If he wants to return, then pay expiation. And in Surah Al-Mujadalah verses 1-4 about zhihar, the law of zhihar is a grave sin that is not punished by divorce and those who wants to return must pay expiation. From As-babun Nuzul then, Islam has raised the degree of women. Ila and zhihar are closely related to gender inequality or bias. Husband as a man has a superpower in controlling women, namely his wife. From this, M. Quraish Shihab explains in his gender equality verses that men and women have the same position, to help each other help and love each other. Even if there is a verse regarding the husband's position as the leader, then that too must not injure the rights of the wife. Keywords : Ila, zhihar, gender, Quraish Shihab Abstrak : Ila dan zhihar adalah salah satu jenis sebab putusnya perkawinan pada masa jahiliyah. Ila merupakan sumpah suami untuk tidak menggauli istrinya lagi. Sedangkan zhihar adalah pekataan suami yang menyamakan punggung istri sama dengan punggung ibunya. Dahulu para suami semena-mena terhadap istri. Ila pada masa jahiliyah lebih dari 2 tahun. Sehingga istri digantung tidak diberi kepastian dalam waktu yang lumayan lama. Begitu juga dengan Zhihar pada masa jahiliyah. Para suami seenaknya menzhihar istrinya, dan menjadikan hal itu sebagai putus perkawinan. Setelah turun ayat 226-227 QS. Al-Baqarah tentang ila, maka suami yang mengila istrinya diberikan waktu tangguh 4 bulan. Jika ia ingin kembali maka membayar kafarat. Dan Dalam surat Al-Mujadalah ayat 1-4 tentang zhihar, bahwa hukum zhihar adalah dosa besar, tidak dihukumi talak dan yang ingin kembali harus membayar kafarat. Dari Asbabun Nuzul tersebut maka, Islam telah mengangkat derajat perempuan. Ila dan zhihar erat sekali hubungannya dengan ketimpangan atau bias gender. Suami sebagai seorang laki-laki memiliki superpower dalam mengendalikan perempuan yaitu istrinya. Dari hal tersebut, M. Quraish Shihab menerangkan dalam ayat-ayat kesetaraan gendernya bahwa laki-laki dan perempuan memiliki kedudukan yang sama, untuk saling tolong menolong dan saling mengasihi. Kalaupun terdapat ayat yang tentang kedudukan suami sebagai pemimpinnya, maka itupun tak boleh mencederai hak-hak istri. Kata Kunci : Ila, zhihar, gender, Quraish Shihab